PENGARUH MOTIVASI KERJA DAN SISTEM KOORDINASI TERHADAP PRESTASI KERJA PEGAWAI PADA BAGIAN LAYANAN PENGADAAN BARANG DAN JASA SEKRETARIAT DAERAH KABUPATEN LAMPUNG TENGAH - Efa Maya Sari (Universitas Muhammadiyah Metro Lampung, 2019)
The results of study showed that work motivation was statistically significant and positive for work performance. The coordination system statistically has a positive and significant effect on employee performance. Work motivation and coordination systems jointly influence positively and significantly on employee performance. Based on the regression results, the coefficient of determination shows a number of 0.391. This result can be interpreted that motivation and coordination system can influence the work performance of employees in the Goods and Services Procurement Service Section of the Central Lampung Regency Secretariat of 39.1%, while the remaining 60.9% of the employee's work performance in the Secretariat of Goods and Services Procurement Services Division Central Lampung Regency is influenced by other variables not examined. Keywords: work motivation, coordination system, work performance